Progression of endolymphatic hydrops in Ménière's disease as evaluated by magnetic resonance imaging - Fiorino, Francesco; Pizzini, Francesca B; Beltramello, Alberto; Barbieri, Franco (Otology & neurotology, 2011)
To evaluate the presence and the degree of endolymphatic hydrops (EHs) in patients with unilateral Ménière's disease (MD), as a function of duration of the disease, estimated using a 3-dimensional fluid-attenuated inversion recovery sequence in a 3-Tesla magnetic resonance imaging unit, after intratympanic gadolinium administration. A total of 32 patients (21 male and 11 female subjects, aged 25-78 yr; median, 56 yr) participated in the investigation. The duration of the disease ranged from 2 months to 10 years (median, 3 yr), with a prevalence of vertigo spells in the last 6 months ranging from 0.5 to 8 per month (median, 2.5). A 0.6-ml solution of gadobutrol (1 mmol/ml) diluted 1:7 in saline was injected in the affected ear through the inferior-posterior quadrant of the tympanic membrane, using a 22-gauge spinal needle. The patient was kept with the head rotated 45 degrees contralaterally for 30 minutes after each injection. Twenty-four hours later, a 3-dimensional fluid-attenuated inversion recovery magnetic resonance imaging was performed. Perilymphatic enhancement was evaluated in different portions of the labyrinth as a function of MD duration. Reduced or absence of enhancement of the vestibule occurred precociously and occurred in all subjects at long term. The prevalence of enhancement abnormalities in the cochlea and the semicircular canals was directly proportional to MD duration. At long term, the vestibule and the cochlea showed a more severe hydropic involvement compared with semicircular canals. A statistical significant correlation between enhancement abnormalities and MD duration was observed for most inner ear sites. The increased prevalence and severity of EH with the duration of MD indicates that hydrops is a progressive degenerative phenomenon. The frequent abnormality in the vestibule and, secondarily, in the cochlea is in line with some histopathologic investigations. It remains to be clarified whether hydropic changes are related to specific signs and symptoms of MD.